High-throughput kinome-RNAi screen identifies protein kinase R activator (PACT) as a novel genetic modifier of CUG foci integrity in myotonic dystrophy type 1 (DM1). - Nafisa Neault (Public Library of Science (PLoS), 2021)
Myotonic Dystrophy Type 1 (DM1) is the most common form of adult muscular dystrophy (~1:8000). In DM1, expansion of CTG trinucleotide repeats in the 3' untranslated region of the dystrophia myotonica protein kinase (DMPK) gene results in DMPK mRNA hairpin structures which aggregate as insoluble ribonuclear foci and sequester several RNA-binding proteins. The resulting sequestration and misregulation of important splicing factors, such as muscleblind-like 1 (MBNL1), causes the aberrant expression of fetal transcripts for several genes that contribute to the disease phenotype. Previous work has shown that antisense oligonucleotide-mediated disaggregation of the intranuclear foci has the potential to reverse downstream anomalies. To explore whether the nuclear foci are, to some extent, controlled by cell signalling pathways, we have performed a screen using a small interfering RNA (siRNA) library targeting 518 protein kinases to look at kinomic modulation of foci integrity. RNA foci were visualized by in situ hybridization of a fluorescent-tagged (CAG)10 probe directed towards the expanded DMPK mRNA and the cross-sectional area and number of foci per nuclei were recorded. From our screen, we have identified PACT (protein kinase R (PKR) activator) as a novel modulator of foci integrity and have shown that PACT knockdown can both increase MBNL1 protein levels; however, these changes are not suffcient for significant correction of downstream spliceopathies.